Pengaruh Perbandingan Tepung Kacang Ginkgo (Ginkgo Biloba L.) Dengan Nanas Kering (Ananas Cosmosus (L) Merr.) Terhadap Karateristik Snack Bar - Johan, Jason; Ekawati, I Gusti Ayu; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2022)
This study was aimed to determine the effect of ginkgo nut powder comparison with dried pineapple to the characteristics of snack bar and the exact comparison between ginkgo nut powder with dried pineapple that was able to produce snack bar with the best characteristics.The experimental design used was Completely Randomized Design with the treatment composition of ginkgo nut powder and dried pineapple consisting of 5 levels: 70%:30%; 60%:40%; 50%:50%; 40%:60% and 30%:70%. The treatment was repeated 3 times to obtain 15 units of experiment. The obtained data was analyzed by ANOVA and if the treatment had significant effect on the observed variables then continued with Duncan,s Multiple Range Test (DMRT). The comparison of ginkgo nut powder and dried pineapple fruit significantly affected water content, ash content, fat content, protein content, carbohydrate content, total calories, antioxidant activity, color (hedonic test), aroma (hedonic test), texture (hedonic and scoring test), taste (hedonic test) and overall acceptance (hedonic test) of the snack bar. Comparison of 30% ginkgo nut powder: 70% dried pineapple had the best characteristic of snack bar with criteria water content 15.23 %, ash content 3.08 %, fat content 18.90 %, protein content 3.84 %, carbohydrate content 58.92 %, total calories 421.26 kkal, antioxidant activity 66.74 %, color was normal, aroma was normal, taste was normal, overall acceptance was moderately liked and texture was a bit hard and normal.